2014
DOI: 10.1002/pbc.24960
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of being overweight or obese in survivors of pediatric acute lymphoblastic leukemia (ALL)

Abstract: Background A high prevalence of obesity has been increasingly recognized in survivors of pediatric ALL. However, longitudinal patterns of weight change during and after treatment, and associated factors, are less well elucidated. Procedure In a retrospective cohort of 83 pediatric patients with ALL diagnosed between 1985 and 2010, we examined body mass index (BMI) status at several key time points: diagnosis; end of induction; end of consolidation; every 6 months during maintenance; and yearly for up to 5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(107 citation statements)
references
References 36 publications
12
87
1
7
Order By: Relevance
“…However, we recently reported that adult cancer survivors had worse overall diet quality than age-and sexmatched controls in the NHANES, and survivorsÕ intake patterns were particularly worse for fiber and empty calories than those in the general population (28). We need to keep in mind that childhood cancer survivors experience a substantially higher chronic disease burden than the general population (2,22,23). Even when diet quality in the survivors and general population is similarly poor, poor diet can have a much larger impact on overall health in long-term childhood cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we recently reported that adult cancer survivors had worse overall diet quality than age-and sexmatched controls in the NHANES, and survivorsÕ intake patterns were particularly worse for fiber and empty calories than those in the general population (28). We need to keep in mind that childhood cancer survivors experience a substantially higher chronic disease burden than the general population (2,22,23). Even when diet quality in the survivors and general population is similarly poor, poor diet can have a much larger impact on overall health in long-term childhood cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
“…These intake patterns are established risk factors for chronic diseases such as cardiovascular disease, diabetes, and obesity. The remarkably high chronic disease burden and early onset of chronic diseases in this population (2,22,23) reinforce the need to incorporate nutrition into cancer care to improve diet quality and to reduce morbidities in the growing number of children who have survived cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity also affects a substantial proportion of ALL survivors with a prevalence of 34-46% at 10 years of follow-up (184). Although cranial irradiation represents a significant risk factor of obesity and diabetes mellitus in ALL survivors (185), those treated with chemotherapy alone continue to experience high rates of persistent obesity and overweight after many years of follow-up, likely because of their prolonged exposure to high-dose glucocorticoids (186). Patients treated with HSCT do not seem to experience higher rates of obesity than similar aged individuals from the general population, but they were reported to have increased risks of insulin resistance, glucose intolerance and abnormal body composition (187).…”
Section: Prevalence and Risk Factorsmentioning
confidence: 99%
“…Research on overweight prevalence has involved mostly ALL survivors (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), whereas study of risk factors has led to inconsistent conclusions (4). Studies conducted in the United States reflect the lifestyles and eating habits of CSSs in that country (10-13, 16, 17, 19-22), whereas the duration of follow-up in other studies has been only short to medium term (4,5), and many have had small (<250 participants) sample sizes (4,11,(13)(14)(15)(17)(18)(19). With this background of research in mind, we analyzed data from the Swiss Childhood Cancer Survivor Study (SCCSS) to 1) assess overweight prevalence in CCSs overall and for specific, different diagnoses; 2) compare overweight prevalence in CCSs with that in their siblings and the Swiss general population; and 3) identify sociodemographic and clinical risk factors for excessive weight.…”
Section: Introductionmentioning
confidence: 99%